Prevalence of small for gestational age term neonates and its surrogate marker - S., Satyamanasa Gayatri Vinay; K., Karthiga; Shrivastava, Abhijeet (International Journal of Contemporary Pediatrics, 2019)
Background: The incidence of low birth weight babies continues to be high in India at about 30% in contrast to 5-7% in developed countries. Perinatal, neonatal and infant mortality as well as morbidity is associated with low birth weight (LBW) neonates of which, it is the Small for Gestational Age (SGA) neonates that are at increased risk. Henceforth, it becomes important to study the prevalence of SGA babies and to compare various anthropometric measurements among term neonates for assessing as to which of these could be taken as surrogate markers of small for gestational age babies. Methods: It was a cross sectional study conducted over a period of 2 years among 100 term neonates delivered in a private medical college in Puducherry, India. Results: The prevalence of low birth weight babies and small for gestational age was found to be 40% and 30% respectively. Using mid arm circumference as a predictor, the sensitivity, specificity, positive predictive value and negative predictive value of SGA was found to be 100%, 57.14%, 50% and 100% respectively. Using MAC/HC ratio as a predictor, the sensitivity, specificity, positive predictive value and negative predictive value was found to be 46.67%, 100%, 100% and 81.4% respectively. Conclusions: In predicting SGA babies, mid arm circumference has the highest sensitivity whereas MAC/HC ratio has the highest specificity followed by mid arm circumference. Present study concluded that mid arm circumference and ratio of MAC/HC are very helpful in identifying SGA neonates among term neonates.